Keikutsertaan Kelas Ibu Hamil Berhubungan dengan Tingkat Kecemasan Ibu Hamil Menghadapi Persalinan di Puskesmas Pleret - Anna Talia Salsa Bella; Suyani Suyani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Pregnancy is a significant phase in a woman's life, characterized by physiological and psychological transformations. The World Health Organization (WHO) indicates that almost 820 million pregnant women suffer from mental health issues, including anxiety. The Indonesian Ministry of Health reported that the incidence of anxiety among pregnant women is 43.4% during pregnancy and escalates to 48.7% before the childbirth. This significant figure indicates the necessity for promotional and preventive initiatives to enhance the mental preparedness of pregnant mothers. Possible interventions include participation in prenatal classes. This study aims to determine the relationship between participation in prenatal classes and maternal anxiety levels regarding childbirth at the Puskesmas (Community Health Center) Pleret. The research employed an observational analytical design with a cross-sectional methodology. The study population consisted of all pregnant women receiving prenatal examinations at the Puskesmas Pleret, with a sample of 32 respondents selected by total sampling technique. Data was collected through a prenatal class participation questionnaire and the Perinatal Anxiety Screening Scale (PASS) instrument. Bivariate analysis was conducted with the Spearman Rank test. The study's results indicated a significant relationship between participation in prenatal classes and anxiety levels among pregnant women in the third trimester, with a p-value of 0.000 (p < 0.05) and a correlation coefficient of 0.752, indicating a strong and unidirectional relationship. Participation in prenatal classes significantly contributes to reducing anxiety levels in pregnant women before childbirth.